Endogenous ligands of bovine FFAR2/GPR43 display distinct pharmacological properties - Michelotti, Tainara Cristina; Lamothe, Valérie; Jean-Alphonse, Frédéric; Reiter, Eric; Bonnet, Muriel; Durand, Guillaume (Frontiers in Cell and Developmental Biology, 2025)
IntroductionFree fatty acids (FFAs) have been identified as ligands for members of the G protein-coupled receptor (GPCR) family, called free fatty acid receptors (FFARs). Among these receptors, there is a particular interest in the physiological roles of FFAR2 and its potential use as a therapeutic target for various health disorders. Despite great progress in other species, pharmacological properties of the bovine FFAR2 (bFFAR2) are not fully understood. The aim of the current study was to evaluate how a selection of FFAs (C2:0 to C8:0, and branched FFAs) activate and regulate bFFAR2 signaling.MethodsWe used HEK293A cells and BRET assays to measure Gαi/Gαq coupling and signaling, β-arrestin 2 recruitment, and receptor internalization/trafficking. SRE and NFAT-RE dependent transcription was assessed by luciferase reporter assay.Results and discussionResults show that bFFAR2 presents a dual coupling to Gαi and Gαq and recruits β-arrestin 2 when stimulated with short and medium-chain FFAs up to eight carbons. Straight-chain FFAs with 4 to 7 carbons plus 3-methyl-butanoic acid showed the greatest potency to activate bFFAR2 upstream and downstream signaling, while C2:0, C3:0 and 2-methylpropanoic acid (2MP) were the least potent. 2MP exhibited minimal pharmacological activity towards β-arrestin 2, and although it induced receptor internalization, bFFAR2 trafficking to the early endosome was not observed. Overall, the number of carbons of straight-chain FFAs and methyl position of branched FFAs differentially regulates the activation of bFFAR2.